Chapter 2 Demonic Daydreams Mind-Wandering and Mental Imagery in the Medieval Hagiography of St Dunstan - Powell, Hilary (Boydell & Brewer, 2018)
"St Dunstan stood in his ivied tower, Alembic, crucible, all were there; When in came Nick to play him a trick, In guise of a damsel passing fair. Every one knows How the story goes: He took up the tongs and caught hold of his nose".2 Richard Harris Barham was correct in his 1837 lay lampooning the legend of St Dunstan: the tale of the saint tweaking the devil's nose was indeed one which everyone knew. In fact, so famous was the tale that Barham felt it needed no further explanation.3 Few in the nineteenth century, however, could have known of its origins, nor indeed have imagined its novelty when the story first entered the hagiographical tradition in the final decade of the eleventh century. St Dunstan (909-988) had been dead for over a century and at least two different accounts of his Life had already been written, but Osbern of Canterbury was the first to tell this tale in his Vita S. Dunstani, written c. 1090.4 This essay explores the origins of this story, addresses why Osbern chose to introduce it into the legend of Dunstan, and asks what his careful remodelling of the tale can reveal about the purposes of hagiographical narratives.